Evaluation of Reference Evapotranspiration Equations under Current Climate Conditions of Egypt - Gamal El Afandi; Mohamed Abdrabbo (Turkish Journal of Agriculture: Food Science and Technology)
Precise estimation of the reference evapotranspiration is very important and vital in different fields such as agriculture, hydrology and meteorology. The aim of the current study was to evaluate the performance of different reference evapotranspiration methods compared to Class-A pan or E-pan over different agro-climatic regions in Egypt. In this study, Egypt has divided into several agro-climatic regions according to the average air temperature and the reference evapotranspiration from Class-A pan. These were Nile Delta in the north, middle and Upper Egypt. Four reference evapotranspiration (ETo) methods namely; Blaney-Criddle, Hargreaves, Thornthwaite and FAO-56 Penman-Monteith (PM) have been evaluated in this study. The results revealed that, there were statistically no significance between E-Pan and PM at P-value less than 0.05, while the other equations had significant differences. The Hargreaves equation reported the highest ETo value at all regions while Thornthwaite was the lowest one. The difference percentage ratios between FAO-56 Penman-Monteith, Blaney-Criddle, Thornthwaite and Hargreaves and E-Pan were 3.7, -13.3, -24.8 and 10.7 respectively. Hence, FAO-56 Penman-Monteith method has proved its capability in estimation of reference evapotranspiration over different agro-climatic regions in Egypt. Therefore, it could be used over any region in Egypt especially those have no reference evapotranspiration instruments.This study is a regional research, similar studies has been made for different regions by many researchers. Therefore, the determined results in this study can be used for regions with similar climatic conditions.